Kegiatan Rehabilitasi Kerusakan Sanggar Karang Taruna Desa Senggigi Pasca Gempa Lombok 2018 - Ni Nyoman Kencanawati; Fathmah Mahmud; Nuralifa Dea Octavia; Dewandi Saputra (Universitas Mataram, 2022)
considerably satisfying progress. It can be seen that most of the village roads have been paved to meet community needs in supporting economic progress and tourism. However, the Lombok island strong earthquake in 2018 damaged facilities and infrastructures because the location of Senggigi was close to the epicenter of the earthquake. One of the damages occurred at the youth organization center in Kerandangan Sub-village. The purpose of this community service is to assist in repairing the center; therefore it can operate normally. The method used is divided into several stages. The first stage is an assessment of the damage to ensure whether the center can be rehabilitated economically. The second stage is to collect data on the details of the damage. The third stage is to decide which repairs will be made and the materials to be used. The last stage is rehabilitation activities. This work was carried out in approximately two weeks with the community self-financing fee and directed by the community service team. The Senggigi Village Head has re-inaugurated the center and is expected to be used according to its previous function by the children and youth of Senggigi Village.